Health Services for Elderly In Panti Werdha Karitas Cimahi - Heni Purnama (Indonesian Journal of Community Development, 2021)
The nursing home is one of the health services for the elderly, but not all nursing homes have adequate facilities and human resources to provide optimal services in improving the welfare of the elderly. The purpose of this community service is to provide health services to the elderly which include health checks, activity therapy, massage therapy, and health consultations. The method of activity is community services from nurse to elderly. Elderly know their health status and feel relaxed after being given health services by nurses. The elderly will benefit from the implementation of this activity and hope that the activities will be carried out in an orderly manner every month. It takes cooperation and coordination with the manager of the nursing home and also the puskesmas as primary health service providers.